2019
DOI: 10.2337/dc18-2005
|View full text |Cite
|
Sign up to set email alerts
|

Promises and Perils of Group Clinics for Young People Living With Diabetes: A Realist Review

Abstract: Group clinics are becoming popular as a new care model in diabetes care. This evidence synthesis, using realist review methodology, examined the role of group clinics in meeting the complex needs of young people living with diabetes. Following Realist And Meta-narrative Evidence Synthesis-Evolving Standards (RAMESES) quality standards, we conducted a systematic search across 10 databases. A total of 131 articles met inclusion criteria and were analyzed to develop theoretically informed explanations of how and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“… 32 , 33 , 35 , 36 Instead of a single standardised format, the literature proposes common organising principles for successful delivery of VGCs (and technology-supported care in general), including attention to the role of patients as active co-production partners, and reconfiguration of care delivery so that VGCs provide added value. 13 , 37 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 , 33 , 35 , 36 Instead of a single standardised format, the literature proposes common organising principles for successful delivery of VGCs (and technology-supported care in general), including attention to the role of patients as active co-production partners, and reconfiguration of care delivery so that VGCs provide added value. 13 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…2 , 8 12 Combining clinical care with elements of group education and peer support, group consultations have been delivered in a variety of formats for patients with long-term conditions or shared health concerns. 8 , 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel approaches, such as group consultations (or ‘shared medical appointments’), have been employed to address current shortcomings in diabetes care delivery [ 16 – 21 ]. Group consultations bring together clinical experience and patient expertise to provide an alternative means of service provision, where small groups of patients attend jointly for their clinical consultations and at the same time have the opportunity to share with peers [ 22 ]. Extending beyond patient education, self-management, and peer support programmes (long established in diabetes care), it has been suggested that group consultations contribute towards improvement of clinical and patient-reported outcomes [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of group visits in adult patients with T1D has not been defined. A recent analysis 10 assessing whether—based on the group care models existing in the literature—group visits may or may not work for young patients with diabetes, identified four general principles that can be applied in different contexts to support the involvement in group visits: (a) emphasize self‐management as practical knowledge, (b) develop a sense of affinity between patients, (c) provide safe and adequate care, and (d) balance individual and group needs. The few reports available on group visits in patients with T1DM mainly regard adolescents/young people, 11 , 12 with no data in adults with T1DM using pump and innovative technologies.…”
Section: Introductionmentioning
confidence: 99%